Soil Moisture and Soluble Salt Content Dominate Changes in Foliar δ13C and δ15N of Desert Communities in the Qaidam Basin, Qinghai-Tibetan Plateau - Niu, Weiling; Chen, Hui; Wu, Jianshuang (Frontiers in Plant Science, 2021)
Changing precipitation and temperature are principal drivers for nutrient cycling dynamics in drylands. Foliar isotopic carbon and nitrogen composition (δ13C and δ15N) are often used to describe plant's water use efficiency and nitrogen use strategy in plant ecology research. However, the drivers and mechanisms under differential foliar δ13C and δ15N among species and communities are largely unknown for arid high-elevation regions. This study collected 462 leaf samples of ten top-dominant species to measure the community-weighted means (CWMs) of foliar δ13C and δ15N across 16 sites in 2005 and 2010, northeastern Qaidam Basin, Qinghai-Tibetan Plateau. Our results showed that the CWM of foliar δ15N was higher in 2005 than in 2010 and was lower in the warm-wet season (Jun-Jul) than the cool-dry one (Aug-Sep) in 2010. Similarly, the CWM of foliar δ13C was higher in 2005 than in 2010 but no difference between warm-wet and cool-dry seasons in 2010. C4 plants have higher δ13C and generally grow faster than C3 species under warm-wet weathers. This might be why the CWM of foliar δ13C was high, while the CWM of foliar δ15N was low in the wet sampling year (2010). The general linear mixed models revealed that soil moisture was the most critical driver for the CWM of foliar δ15N, which explained 42.1% of the variance alone. However, the total soluble salt content was the crucial factor for the CWM of foliar δ13C, being responsible for 28.7% of the variance. Growing season temperature (GST) was the second most vital factor and explained 28.0% and 21.9% of the variance in the CWMs of foliar δ15N and δ13C. Meanwhile, remarkable differences in the CWMs of foliar δ15N and δ13C were also found among species. Kalidium gracile and Salsola abrotanoides have higher foliar δ15N while Ephedra sinica and Tamarix chinensis have lower foliar δ15N than other species. The foliar δ13C of Calligonum Kozlov and H.ammodendron was the highest among the ten species. Overall, the CWM of foliar δ15N and δ13C dynamics were affected by soil properties, wet-dry climate change, and species identity in high-elevation deserts on the Qinghai Tibetan Plateau.